Proba the Prophet : The Christian Virgilian Cento of Faltonia Betitia Proba - Schottenius Cullhed, Sigrid (Mnemosyne, Supplements, Late Antique Literature Ser, 2015)
Contents -- Acknowledgements -- List of Figures -- Introduction -- Chapter 1. Proba the Poet -- Chapter 2. Proba and Her Critics -- Chapter 3. Proba in the Republic of Women -- Chapter 4. The Confessions of Proba -- Chapter 5. Centonizing Genesis -- Chapter 6. The Gospel of Proba -- Appendix. The Cento of Proba -- Bibliography -- Index Locorum -- General Index.